The impact of trust in eWOM through dimensions of source credibility towards purchase intention of a hotel stay - Lundin, Hanna (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
The purpose of this study was to investigate how trust was built from three dimensions of source credibility in an electronic word of mouth space towards purchase intentions of a hotel stay. The chosen dimensions of Source Credibility that were investigated in the study was: Homophily, Expertise and Trustworthiness. The study aimed to see how consumers of hotel booking for a destination got affected and believed in electronic word of mouth for their intention to purchase a hotel stay via the internet. A quantitative method was chosen for this study with a questionnaire that was sent out to students on the programmes “Ekonomie Kandidat”, “Civilekonom” and “Fastighetsmäklare” at Luleå University of Technology. The questionnaire was also shared on the author's private Facebook page and sent to friends and family via messenger. The data was collected during one week and summarized in diagrams and a one-sample statistical t-test for the three dimensions of Source Credibility were run and are provided in appendix 1-3. The findings for this study shows that all three dimensions; homophily, trustworthiness and expertise impact trust in eWOM and can lead to purchasing intentions of a hotel stay. The trust towards an expert who works at a hotel (manager) did not seem to be trustworthy compared to previous customers who shared their opinions of a hotel online. It appeared clearly that previous customer reviews which provide a lot of information, repetitive reviews of customers and new reviews are seen as the most trustworthy for purchasing a hotel stay online. A recommendation to managers in the hotel industry and to those working with the review websites is therefore to categorize reviews so customers easily can pick from what they are searching for.